Thermoelectric properties of Na-doped Zintl compound: Mg3−xNaxSb2. (July 2015) - Shuai, Jing; Wang, Yumei; Kim, Hee Seok; Liu, Zihang; Sun, Jingying; Chen, Shuo; Sui, Jiehe; Ren, Zhifeng
Abstract: Mg3− x Na x Sb2 has been prepared successfully by mechanical alloying plus hot pressing to investigate the effects of Na doping on the thermoelectric properties. Thermoelectric properties were characterized by the Seebeck coefficient, electrical resistivity, thermal conductivity, and thermoelectric figure of merit ( ZT ) from 298 to 773 K. Transport measurements reveal that an optimum doping of 1.25 at.% Na on Mg achieved ZT of 0.6 at 773 K. The enhancement in ZT is attributed to increased carrier concentration and power factor. The low cost, abundance, and nontoxicity makes this material a potentially promising thermoelectric material for power generation at a heat source below 773 K.